Retinal vascular calibers and correlations with biomarkers in bitches with pyometra-induced systemic inflammatory response syndrome - Fábio Dumit Pizzinatto; Alexandre Pinto Ribeiro; Bianca Eidt Rodrigues; Hanna Rodrigues Miranda; Nathalia de Assis Pereira (Veterinary World)
Background and Aim: Pyometra is a common uterine disease in intact bitches, frequently progressing to systemic inflammatory response syndrome (SIRS). While retinal vascular alterations have been observed in human SIRS cases, similar evaluations are lacking in veterinary medicine. This study aimed to evaluate retinal vascular calibers in bitches with pyometra-induced SIRS (P-SIRS) and explore correlations between retinal measurements and hematological, biochemical, vascular endothelial growth factor (VEGF), and interleukin-4 (IL-4) levels.